Strategi Komunikasi Pemasaran Produk Manufaktur di Pasar Domestik Dalam Meningkatkan Brand Awareness: Studi PT. Argha Tehnik Makmur Domestik - Vinaya, Teddy (Prisani Cendekia Institute, 2024)
This study aims to examine the marketing communication strategies employed by PT Argha Tehnik Makmur to boost awareness of its manufacturing products in the domestic market. This research employs the STOPSIT model and uses qualitative methods by conducting interviews with key individuals such as the director, manager, and marketing supervisor of PT Argha Tehnik Makmur. It was discovered that the company has effectively executed market segmentation strategies in its business operations. The company recognizes and differentiates the demands and characteristics of several market areas, such as the food industry, pharmaceuticals, autos, and distribution networks encompassing couriers and minimarkets. The research findings also suggest that PT Argha Tehnik Makmur's understanding of the different demands and characteristics of each market category allows them to personalize their products, price, distribution, and promotion accordingly. By implementing market segmentation, PT Argha Tehnik Makmur is able to allocate resources in a more efficient manner and design marketing strategies that are more focused. This leads to improved marketing effectiveness and increased efficiency in production and marketing operations. Consequently, by using the market segmentation approach, PT Argha Tehnik Makmur has enhanced its market position, heightened competitiveness, and ultimately facilitated total business expansion and success.